Economic Implications of Ageing Lithuanian Population - Kasnauskienė, Gindra; Andriuškaitė, Marija (Organizations and Markets in Emerging Economies, 2017)
Increased life expectancy combined with declining birth rates and massive emigration flows have caused many to worry about the various impacts of an ageing population in Lithuania. This suggests a very big increase in the dependency ratio and is consequently a cause for concern about a future slowing of economic growth. However, there is little research carried out regarding economic or financial effects of this phenomenon in the country. The aim of this paper is to evaluate the impact of Lithuanian ageing population on economic variables. A new research design is implemented by using VAR and ARMAX models to compare two different approaches, treating ageing as an endogenous and exogenous variable. The authors find that old age dependency ratio has no statistically significant impact on Lithuania’s GDP growth, employment rate, final household consumption and gross national savings in the short run. The results achieved can be explained by incomplete and only short run data available for Lithuania. Also, joining the EU and other favorable economic conditions might have boosted Lithuania’s economic performance over the whole research period and significantly reduced the negative effects of ageing population. However, the impact of shifts in the structure of population age might soon come into effect, as Lithuania‘s society is gathering the pace of ageing, which is also seen in other emerging markets that are progressing toward becoming advanced.